Optimizing congenital cytomegalovirus detection by pool testing in saliva by a rapid molecular test - Izquierdo, Giannina; Farfan, Mauricio J; Villavicencio, Leonel; Montecinos, Luisa; Tarque, Felipe; Acevedo, William; Reyes, Roberto; Guerra, Carolina; Araya, Leslie; Sepúlveda, Belén; Cabrera, Camila; Medina, Pamela; et al. (European journal of pediatrics, 2023)
Universal congenital cytomegalovirus (cCMV) screening in saliva is increasingly recommended. The aim of our study was to correlate the performance of a point-of-care rapid molecular test with CMV real time PCR (CMV RT-PCR) detection, using saliva pool-testing in newborns under a universal screening strategy. Saliva swabs were prospectively collected from newborns < 21 days old and tested by Alethia-LAMP-CMV assay in pools of 5 samples. In positive pools, subjects were tested individually and by saliva and urine CMV RT-PCR. A subset of negative pools were studied with both techniques and viral loads in whole blood were determined in positive patients. From 1,642 newborns included in 328 pools, 8 were confirmed by urine CMV RT-PCR, (cCMV prevalence 0,49%). The PPA and NNA of the pooled saliva Alethia-LAMP-CMV testing were 87,5% and 99,8% with a negative and positive predictive value of 99,9% and 77,7%, respectively. Two false positives were detected (0,12%). A subset of 17 negative pools (85 samples), studied by saliva CMV RT-PCR, showed 100% concordance.